Mammoth math : (with a little help from some elephant shrews) - Macaulay, David (DK, 2022)
The inquisitive mammoths are back, and this time they want to know all about mathematics. Readers and mammoths begin with simple counting, even something so simple as counting on one's fingers--or, for mammoths, their tusks and trunk--and progress up through measuring areas, understanding the importance of the number zero, operations, geometry, and interpreting data. Includes illustrations and a glossary.